Education on Rural Construction Issues in Lithuania, 1918–1940 - Pilkauskienė, Vigilija (Acta humanitarica academiae Saulensis, 2023)
In this article the education of farmers and craftsmen about the construction of modern farmsteads during interwar period is assessed. Information on the subject was collected from interwar press and archival documents. The main features of modern interwar farmsteads are rational structuring, compliance with hygiene requirements, comfortability and aestheticism. These ideas were propagated by state institutions, although up to the 3rd decade it was not fully established. When the administration of rural construction matters was commissioned to the Žemės ūkio rūmai, the most important works in this direction were carried out. The Construction Department was established in 1929, and the construction technicians who worked there were the key players in the promotion of the conceptual framework. Therefore, their proper training and the provision of the necessary number of specialists was an essential prerequisite for the purposeful education of farmers and building tradesmen.Organising education for farmers one of the main goals was to achieve the largest possible number of persons and thus promote the importance of the implementation of the ideas of modernization of rural construction. Therefore, for this, the periodical press, educational publications, short-term courses and lectures on the issues of improving rural construction and the management of homesteads, as well as exhibitions where construction technologies were demonstrated and specialist advice was provided, were actively used for this. Given the gradual increase in farmers’ interest in the ideas promoted, as well as their active participation in the educational programmes, there is no doubt that the measures chosen were quite successful.Rural craftsmen also played an equally important role in the modernisation campaign. Therefore, since the end of the 1930s, short courses have been organised annually to raise their qualifications. The scope of these works was rising, although it affected only part of craftsmen and did not solve the lack of qualified specialists. In the 4th decade, the new laws and rules of rural building regulation were implemented. Also, the necessity for higher number of qualified construction craftsmen that would be able to implement modern building principles was realized. This resulted in first specialized craft schools for carpenters, masons and furnace workers. It was thought that these schools together with earlier courses had to form construction craftsmen education system. Although work in this direction was halted shortly afterwards, the establishment of the specialised schools was an indication of the prioritisation of construction issues and thus of the implementation of modernisation principles.
Keywords: rural construction; education of craftsmen; education of farmers; Žemės ūkio rūmai; construction of modern farmsteads